Fitness cardiorespiratorio y los niveles de obesidad post covid-19 en sujetos de 15-18 años del Club Formativo Pobrecito Catarama-Urdaneta, 2022 - Morán Segura, César Argenis (2022)
The present scientific work is focused on a transversal study about considerations referred to the role played by Cardiorespiratory Fitness in the decrease of patients diagnosed as obese, when the pandemic caused by COVID-19 appears, in order to compile the required information, methods of the empirical level and of the theoretical level of scientific research were used, the former with the purpose of compiling the required information to comply with the programmed objectives, while the latter had the purpose of analyzing the obtained results; consideration that led us to reach our own conclusions. The importance and at the same time the feasibility of the findings obtained lies in the methodological tools that are essentially provided to teachers to facilitate the work that guarantees an optimal relationship between weight and height, not only of the chosen athletes, but also of the population in general, data that supports the scope of the content of this case study; which can be used in other institutions, both sports and educational, where subjects classified as obese appear.